Basis for developing the indicators of the library site performance - S. K. Kann (Библиосфера)
The report discusses approaches to creating the system of statistical indecators for a library website to track their inner dynamics and to compare it with indicators of other sites. Measures are suggested to develop library web-analytics and to make a comprehensive assessment of library sites.